Training the Trainees in Radiation Oncology with Telemedicine as a Tool in a Developing Country: A Two-Year Audit - Sushma Agrawal; Anil Kumar Maurya; Kirti Shrivastava; Shaleen Kumar; M. C. Pant; Saroj Kant Mishra (International Journal of Telemedicine and Applications)
Purpose. The estimated new cancer patient load in the Indian state of Uttar Pradesh is 0.1–0.12 million per year. Approximately two thirds of these require treatment by a radiation oncologist. Radiation oncologists: cancer patient ratio in this state is 1 : 2000 as compared to the recommended 1 : 250. This problem is compounded by the poor infrastructure of radiation oncology departments in the state which is suboptimal for teaching, training of resident doctors, and treatment in most barring a few departments. To bridge some gap in the sociodemographics stated above and enhancement of training of residents, we submitted a project for establishment of a telemedicine facility in our department to the Department of Science and Technology, Government of India. We present the design, implementation, and a two-year audit of our tele-education activities. Materials and Methods. After the sanction of the project, we established telemedicine linkage with another medical institute in the city located 25 kms away in 2007. After implementation of the project, academic sessions designed for trainee residents in our department were shared with the remote end. A record of these activities and a feedback of the activities were audited at the end of 2 years of implementation of this project. Results. Regular videoconferencing sessions comprising of lectures on clinical oncology, medical physics, and radiobiology were held. Feedback from the users revealed satisfaction with the content of the academic sessions for the purpose of MD training. Conclusions. Distance education in radiation oncology is an important tool for training of the trainee residents.